Pengaruh Lama Perebusan Kedelai (Glycine max. L) Menggunakan Autoclave Terhadap Senyawa Fitokimia Tempe - Sri Rahayu, Patricia; Yudiono, Kukuk; Nendra Prasetya, Hendrikus (Fakultas Pertanian, 2024)
Tempe is a traditional Indonesian food, a processed product made from soybeans which is formed from the Rhizopus Sp type mold, especially from the R. oligosporus species through a fermentation process. The tempeh production process needs to be improved in terms of time efficiency, cost, workmanship effectiveness and nutrition. This improvement can be done by boiling the soybeans in an autoclave. Soybeans contain antioxidant compounds in the form of isoflavones, tocopherol and ascorbate. Antioxidants are really needed by the body as an antidote to free radicals because they work by donating one electron to compounds that are oxidants so that the negative impact of oxidants can be inhibited. The aim of this research was to determine the effect of boiling time for soybeans (Glycine max L.) in an autoclave on phytochemical compounds (total polyphenols, total flavonoids and antioxidants) as well as the sensory properties (color and compactness) of soybean tempeh. This research method uses a non-factorial experimental design prepared with RAL (Completely Randomized Design) which consists of 1 factor, namely the length of boiling soybeans in an autoclave with 4 treatment levels P1 (5 minutes), P2 (10 minutes), P3 (20 minutes), P4 (30 minutes) and each treatment was repeated 3 times. The results showed that the highest total phenolic content and total flavonoid content were obtained from soybean tempeh with soybean tempeh treatment in an autoclave for 5 minutes, namely 5.33 mgGAE/g and 0.121 mgQE/g, while the highest antioxidant activity was obtained from soybean tempeh with boiling treatment. soya bean. in an autoclave for 30 minutes, namely 11.32%